2003
DOI: 10.1902/jop.2003.74.4.501
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Antiplaque Effects of Mastic Chewing Gum in the Oral Cavity

Abstract: These results suggest that mastic chewing gum is a useful antiplaque agent in reducing the bacterial growth in saliva and plaque formation on teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 17 publications
3
42
0
1
Order By: Relevance
“…41 Conversely, double-blind, randomized studies on 20 dental students were performed to determine whether gum mastic has any antiplaque activity. 44 The results showed that mastic chewing gum may be useful in reducing the bacterial growth in saliva and plaque formation on teeth. Finally, the results of the current study strongly suggest that gum mastic may have antiprostate cancer effect through its suppressive effect on the expression and function of the AR.…”
Section: Discussionmentioning
confidence: 99%
“…41 Conversely, double-blind, randomized studies on 20 dental students were performed to determine whether gum mastic has any antiplaque activity. 44 The results showed that mastic chewing gum may be useful in reducing the bacterial growth in saliva and plaque formation on teeth. Finally, the results of the current study strongly suggest that gum mastic may have antiprostate cancer effect through its suppressive effect on the expression and function of the AR.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Focusing on these treatment options which possess limited effectiveness in high-risk populations and in those with advanced periodontal disease, [6] and associated with adverse side-effects and antibiotic resistance, [7] people are opting for alternative therapeutic and preventative measures which are safe, effective, and free of side effects. [8] Increasing popularity of traditional medicine has led researchers to investigated the adjunctive methods that use nutrients and functional foods to maintain the health status of periodontal tissues; for example, extracts of plants, including mastic exudated from Pistacia lentiscus [9] and macrocarpals from Eucalyptus globulus, [10,11] have also been investigated for their effects on periodontal health, particularly because of their safety.…”
Section: Introductionmentioning
confidence: 99%
“…Pistacia lentiscus mastic is a natural resin derived from the stem and leaves of the mastic tree, P. lentiscus Linn, native to Mediterranean areas (Takahashi et al 2003). Traditional healers used it for the relief of upper abdominal discomfort, stomachaches, dyspepsia and peptic ulcer (Koo et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence has also suggested that P. lentiscus mastic gum exhibits hepatoprotective, cardioprotective, anti-inflammatory and antioxidant properties (Giaginis and Theocharis 2011). Numerous studies showed that P. lentiscus mastic has impressive antibacterial and antimicrobial properties (Takahashi et al 2003). Balan et al (2007) suggested that P. lentiscus mastic gum might be developed into a chemotherapeutic agent for the treatment of human cancer colon and other cancers.…”
Section: Introductionmentioning
confidence: 99%